Peran Kebijakan Pendidikan dalam Pengembangan Kualitas Profesi Guru di SD Negeri Wonorejo - Putri Maulia Sari; Khasbi Ainun Najib; Alfan Hadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Education plays a strategic role in improving the quality of human resources. In this context, teachers serve as central figures who determine the success of the learning process. Teacher professionalism is one of the key indicators in establishing a high-quality education system. This article aims to analyze the role of educational policy in supporting the development of teacher professional quality in Indonesia. The research method used is descriptive qualitative with a literature study approach, utilizing secondary data sources from scientific articles and journals published between 2020 and 2025, accessed through Google Scholar. The results indicate that educational policies in Indonesia have provided a strong legal and regulatory foundation for the development of teacher professionalism, such as Law Number 14 of 2005 and its derivative regulations. These policies regulate qualifications, competencies, certification, and budget support for teachers. In conclusion, educational policy plays a vital role in improving teacher quality through a structured and sustainable system.